2023
DOI: 10.3390/vehicles6010002
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Approaches for Advanced Battery Management System in Electric Vehicle Applications: A Statistical Analysis towards Future Research Opportunities

M. S. Hossain Lipu,
Md. Sazal Miah,
Taskin Jamal
et al.

Abstract: In order to reduce carbon emissions and address global environmental concerns, the automobile industry has focused a great deal of attention on electric vehicles, or EVs. However, the performance and health of batteries can deteriorate over time, which can have a negative impact on the effectiveness of EVs. In order to improve the safety and reliability and efficiently optimize the performance of EVs, artificial intelligence (AI) approaches have received massive consideration in precise battery health diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…𝐿𝑖𝑃𝐹 ⟶ 𝐿𝑖𝐹 + 𝑃𝐹 ⎯ 𝑃𝐹 + 2𝐻𝐹 (16) The synthesis of 𝜆 − 𝑀𝑛𝑂 and the presence of HF have been coupled by Mikheenkova et al to explain Mn migration to the negative electrode, as demonstrated by Equation ( 17) [75].…”
Section: Dissolution Of Transition Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…𝐿𝑖𝑃𝐹 ⟶ 𝐿𝑖𝐹 + 𝑃𝐹 ⎯ 𝑃𝐹 + 2𝐻𝐹 (16) The synthesis of 𝜆 − 𝑀𝑛𝑂 and the presence of HF have been coupled by Mikheenkova et al to explain Mn migration to the negative electrode, as demonstrated by Equation ( 17) [75].…”
Section: Dissolution Of Transition Metalsmentioning
confidence: 99%
“…Recently, battery degradation became an issue of great concern among the researchers around the world [16]. Xiong et al presented a review about the aging mechanism of lithium-ion batteries [17].…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in SoH assessment methodologies, including machine learning algorithms and diagnostic technologies, are driving the development of more intelligent battery management systems capable of real-time monitoring, predictive maintenance, and adaptive control strategies. This proactive approach not only prolongs battery lifespan but also promotes sustainable practices by minimizing premature replacements and optimizing resource utilization and recycling efforts [11,12]. Namely, various advanced techniques are available for predicting the performance of lithium-ion batteries, including molecular dynamics simulations and density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%